#### Wet_Lettuce

##### New Member

Consider the graph of a quadratic function:

y= 2x^2-3x+1

Translate the (x,y) co-ordinate axes horizontally and vertically, so that the new origin of the co-ordinates system is located at the point with the old co-ordinates (3,5).

The new (X,Y) co-ordinates are therefore related to the old (x,y) system by the equations:

X= x-

Y= y-

Substitute these into the formula y=F(x) above, in order to express Y as a function of X. (Be sure to write the simplest form)

Y=

Thanks so much guys